Impact of Nutrient Restriction on the Structure of Listeria monocytogenes Biofilm Grown in a Microfluidic System - Cherifi, Tamazight; Jacques, Mario; Quessy, Sylvain; Fravalo, Philippe (Frontiers in Microbiology, 2017)
Biofilm formation by the pathogen Listeria monocytogenes is a major concern in food industries. The aim of this work was to elucidate the effect of nutrient limitation on both biofilm architecture and on the viability of the bacteria in microfluidic growth conditions. Biofilm formation by two L. monocytogenes strains was performed in a rich medium (BHI) and in a tenfold diluted BHI (BHI/10) at 30°C for 24h by using both static conditions and the microfluidic system Bioflux. In dynamic conditions, biofilms grown in rich and poor medium showed significant differences as well in structure and in the resulting biovolume. In BHI/10, biofilm was organized in a knitted network where cells formed long chains, whereas in the rich medium, the observed structure was homogeneous cellular multilayers. Biofilm biovolume production in BHI/10 was significantly higher than in BHI in these dynamic conditions. Interestingly, biovolume of dead cells in biofilms formed under limited nutrient conditions (BHI/10) was significantly higher than in biofilms formed in the BHI medium. Whereas, in static conditions, biofilm is organised in a multilayer cells and dispersed cells in a rich medium BHI and poor medium BHI/10 respectively. There was significantly more biomass in the rich medium comparing to BHI/10 but no difference was noted in the dead/damaged subpopulation showing how L. monocytogenes biofilm could be affected by the growth conditions. This work demonstrated that nutrient concentration affects biofilm structure and the proportion of dead cells in biofilms under microfluidic condition. Our study also showed that limited nutrients play an important role in the structural stability of L. monocytogenes biofilm by enhancing cell death and liberating extracellular DNA.